A composite intragenic silencer domain exhibits negative and positive transcriptional control of the bone-specific osteocalcin gene: promoter and cell type requirements. - Frenkel, B (1994)
The osteocalcin (OC) silencer is a unique example of exonic sequences contributing to negative transcriptional control of mammalian gene expression. In this paper we demonstrate, using a reporter transfection assay, that multiple elements reside within the OC +24/+151 domain. Thirty-fold repression is mediated by the +49/+104 fragment, experimentally relocated 3' of the poly(A) signal. Deletion of either the +49/+54 protein-coding sequence or the +98/+104 intronic part of this fragment results in loss of repression activity, suggesting a bipartite organization of the +49/+104 silencer. Of particular interest, we have mapped an antisilencer activity to the ACCCTCTCT motif (+40/+48), found in silencers associated with several other genes. Extension of the +49/+104 silencer to include the +24/+48 and/or the +105/+151 sequences results in increased silencer activity up to 170-fold, suggesting the presence of additional silencer elements within these sequences. The activity of the silencer contained within the +24/+151 OC sequence is directed to the basal promoter and is not dependent on 5' distal enhancer elements, including those that mediate responsiveness of OC transcription to vitamin D. The OC silencer represses the heterologous thymidine kinase promoter and is operative in osseous (normal diploid osteoblasts, ROS 17/2.8 osteosarcoma) as well as HeLa cells. Our results, which suggest the presence of at least five regulatory elements downstream of the OC transcription start site, indicate the complexity of sequences that mediate repression of OC promoter activity.